Determinants of job attitudes in the FBI: A multidimensional comparison - Lee, Hyung-Woo (International journal of law, crime and justice, 2020)
Despite volumes of research on the job attitudes of employees in diverse law enforcement agencies, those of the FBI agents have not been sufficiently studied. Analyzing a large-scale nationwide dataset, this study investigates the determinants of job satisfaction, work effort, and turnover intentions of FBI agents. The results indicate that the determinants of job attitudes are substantially different across the type of job attitudes examined. For instance, career advancement opportunities and the practice of performance-based management positively affected job satisfaction but negatively affected work effort. As well, FBI agents tend to find jobs within the federal government when they are dissatisfied with their tasks or career advancement opportunities, whereas they tend to find jobs outside the government when they are dissatisfied with a lack of incentives or monetary rewards. This multidimensional comparison of job attitude factors demonstrates not only the relative strength of each factor but also their limitations as a motivator.